Role of hole depth on mechanical behavior and acoustic emission characteristics of pre-drilled sandstone - Liu, Jiahan; Lei, Ruide (Frontiers in Earth Science, 2025)
To examine the influence of hole depth on the mechanical properties of rock, a series of uniaxial compression tests were performed on six groups of pre-drilled sandstone samples, each with varying depths. Also, multiple physical fields coupled with acoustic emission (AE) and digital image correlation (DIC) systems were synchronously employed to monitor the fracturing process. The study focused on characterizing the cracking fracturing, energy evolution, and fracture patterns in pre-drilled sandstones with different depths. The findings show that the peak strength of the sandstone decreases linearly with the increase of hole depth. The fracture mode transits from simple unilateral spalling to a complex fracture mode characterized by multiple fractures and spalling. AE analysis shows that the deeper the borehole, the lower the AE signal frequency, indicating fewer but more significant fracturing events. With the increase of hole depth, the peak elastic energy of the sample decreases from 29.81 kJ/m3 to 22.65 kJ/m3, and the dissipated energy increases from 4.48 kJ/m3 to 6.25 kJ/m3. Moreover, the AE energy of the pre-drilled sandstone displays distinct multifractal spectrum features under different stress levels. The multifractal spectrum width (Δα) varies from 0.419 to 0.227, suggesting that small-scale fracturing events predominantly govern the failure mechanism. DIC observation shows that the major principal strain concentration mainly occurs around the hole. The monitoring points around the hole show that the cumulative strain at P2 and P6 is significantly higher compared to other regions. Furthermore, it is observed that the stress release pathways originating from newly formed cracks and dislocation slips become more diversified, suggesting a more complex fracturing mechanism.